Pengembangan Media PowerPoint dan Wordwall Berbasis Inkuiri Materi IPAS Kelas IV Sekolah Dasar - Nurul Maftuchatul Ulya; Sri Sami Asih (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aimed to develop and examine the feasibility and effectiveness of interactive learning media based on PowerPoint and Wordwall integrated with the inquiry learning model to improve fourth-grade students’ learning outcomes in IPAS (Integrated Science and Social Studies). Methods – This research employed a Research and Development (R&D) approach using the Borg and Gall model, limited to the field-testing stage. The study was conducted at SDN Wonokerto 1 Demak involving 43 fourth-grade students. Data was collected through interviews, observations, questionnaires, expert validation sheets, and learning outcome tests (pretest and posttest). Data analysis included normality testing, paired sample t-test, and N-Gain calculation using SPSS. Findings – The study found that the developed product is an inquiry-based interactive learning media combining PowerPoint and Wordwall. The material is delivered in a structured manner using various multimedia elements, while interactive game-based activities are incorporated to facilitate practice and assessment. The design follows inquiry learning stages, encouraging students to actively observe, question, explore, and conclude, resulting in improved engagement and deeper conceptual understanding. The product was categorized as highly feasible (93.33% material validation; 91.60% media validation) and showed a moderate improvement in learning outcomes (N-Gain = 63%).Research Implications – This study implies that interactive learning media based on PowerPoint and Wordwall integrated with the inquiry learning model can serve as an innovative alternative to improve students’ learning outcomes, motivation, and engagement in elementary science and social learning. However, this study is limited to a single class in one school and focuses only on the topic of energy transformation, which may restrict the generalizability of the findings.